Hubungan Kematangan Emosi dengan Pengambilan Keputusan Karir pada Siswa Kelas XII SMA - Ananda, Yashinta Rizky (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This research is done because the phenomenon in Senior High School 1 Mijen-Demak. Based on the record of events, itâs found that students of XII class have not seen the emotional maturity and the decision making of career after graduation. The purpose of this research is to find out relation of the emotional maturity and the career decision making. This research is an ex post facto with the quantitative correlation method. The samples used in this research are 114 students. The data collection that is used the emotional maturity and career decision making scale. The data analysis that is used the descriptive percentage and product moment correlation. The research result shows that 99 of students have the high emotional maturity, 98 of the students have the high decision making of career skill, and the sig is 0,000=0%, less than Î±=5% with r=0,348. There is a significant relation between the emotional maturity and the decision making of career in the low level of relationship. So, it can be said that the Ho is rejected and the Ha is accepted.